Long-term (2001–2013) observations of water-soluble dicarboxylic acids and related compounds over the western North Pacific: trends, seasonality and source apportionment - Suresh K. R. Boreddy (Nature Portfolio, 2017)
Abstract To better understand the impact of East Asian pollutants on the molecular composition of marine organic aerosols, we conducted long-term (2001–2013) observations of water-soluble dicarboxylic acids and related compounds in total suspended particulate samples collected at Chichijima Island in the western North Pacific (WNP). Seasonal variations of all the diacids and related compounds showed maxima in winter and spring and minima in summer, except for azelaic acid (C9), which maximized in summer to autumn. The overall annual concentrations of the total diacids, ω-oxoacids and α-dicarbonyls showed an increase during 2001–2013. We found a significant (p < 0.05) decadal increase in the inter-annual trends of pyruvic and glyoxylic (p > 0.05) acids, and methylglyoxal (MeGly). In contrast, phthalic acid (p < 0.05) and glyoxal (Gly) showed a decrease in their trends. We also found a significant decrease in the trend of the Gly/MeGly mass ratios. These results demonstrate that the enhanced concentrations of diacids over the WNP are majorly attributed to the aqueous-phase photooxidation of biogenic volatile organic compounds from East Asia followed by long-range atmospheric transport. Further, positive matrix factorization analysis showed a biogenic photochemical contribution (42%) was the dominant source of oxalic acid in the WNP.